2017
DOI: 10.1007/s11548-017-1575-8
|View full text |Cite
|
Sign up to set email alerts
|

SLIDE: automatic spine level identification system using a deep convolutional neural network

Abstract: A machine learning system is presented that successfully identifies lumbar vertebral levels. The small study on human subjects demonstrated real-time performance. A projection-based augmented reality display was used to show the vertebral level directly on the subject adjacent to the puncture site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 28 publications
0
38
0
Order By: Relevance
“…Two recent studies, namely Pesteie et al ( 2015 ) and Hetherington et al ( 2017 ), exploited artificial neural networks trained with ultrasound images to automatically detect the optimal vertebra level and injection plane for percutaneous spinal needle injections. They used different ML techniques on the same type of medical images.…”
Section: Literature Review: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies, namely Pesteie et al ( 2015 ) and Hetherington et al ( 2017 ), exploited artificial neural networks trained with ultrasound images to automatically detect the optimal vertebra level and injection plane for percutaneous spinal needle injections. They used different ML techniques on the same type of medical images.…”
Section: Literature Review: Resultsmentioning
confidence: 99%
“…The second study reported a real-time scanner system (SLIDE) implementing a pre-trained CNN and a finite-state transducer that automatically detected the patient's vertebral level for the optimal lumbar puncture point (Hetherington et al, 2017 ). The CNN was trained using a transfer learning approach, where an inter-domain knowledge transfer was used as a prerequisite for accurate prediction.…”
Section: Literature Review: Resultsmentioning
confidence: 99%
“…The accuracy of CNN for normal versus affected tissues (DM, PM, and IBM) reached 76.2% which is 3.9% higher than this value of random forests. Hetherington et al designed a spine level identification system employing CNN [ 68 ]. The system can accurately detect the vertebral level so that the anesthesiologist can find the right site to inject the anaesthetic.…”
Section: Ultrasound Cad System With Deep Learning Technologymentioning
confidence: 99%
“…Minimally invasive surgery is another promising strategy for spine deformities; therefore, accurate percutaneous spinal needle insertion procedures are necessary. Hetherington et al (45) developed a real-time system based on deep CNN to classify transverse images of the lower spine, and this method might contribute to the development of a minimally invasive treatment for ADS. To satisfy the goal of verification, screw insertion was performed intraoperatively.…”
Section: Intraoperative Manipulationmentioning
confidence: 99%